SHOULD MONO-UNSATURATED AND POLY-UNSATURATED FAT PREVENTS THEPROGRESSIVITY PREDIABETES ON WOMAN? - Iche Andriyani Liberty; Ratu Ayu Dewi Sartika (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Most evidence showed that women with diabetes mellitus have a higher risk for cardiovascular disease. Prediabetes is a reversible state that can progressive for future complications or regressive to normoglycemic. The weight loss that prevents progressivity from prediabetes can be achieved by regulating dietary composition. The dietary composition may affect pancreatic ?-cell function and insulin sensitivity. Consumption of foods rich in MUFA and PUFA has a positive effect on metabolism, which is associated with an increase in the position of adiponectin, anti-inflammatory cytokines, which increase liver elevation, and reduce atherosclerosis, such as decreased triglycerides, LDL and VLDL and increased HDL. This article explores relevant literature on this subject in order to identify and elaborated the knowledge for further research.